Legal Implementation of Consumer Protection in Sharia and Conventional Pawn Services in Indonesia - Farid, Diana (Journal of Economicate Studies, 2019)
This research investigates the implementation of consumer protection laws in Indonesia’s dual pawn service systems: Sharia-based (rahn) and conventional pawnshops. Using a normative juridical approach and document analysis, the study evaluates legal enforcement, transparency, and consumer fairness in both contexts. Sharia pawnshops exhibit stronger ethical alignment, guided by maqasid al-shariah principles like fairness (‘adl) and wealth preservation (hifz al-mal), yet suffer from weak institutional oversight. In contrast, conventional pawnshops follow statutory regulations but often lack meaningful enforcement, leading to transparency and compliance issues. The study identifies systemic gaps due to fragmented regulation and low legal literacy among consumers. It proposes harmonizing legal and ethical standards through contract standardization, unified oversight, and legal codification of Islamic ethical obligations. The findings offer novel insights into regulatory pluralism and contribute to the formulation of equitable, consumer-centric financial governance policies in Indonesia.